Kebijakan Hukum Eksploitasi Seksual Terhadap Anak dalam Perspektif Viktimologi - Nadillah Maudi Cahyani; Rida Kherin Oktavianty (Yayasan Miftahul Ulum Sangatta Kutai Timur (KEP. MENKUMHAM RI No. AHU-0014779.AH.01.04.Tahun 2018) bekerjasama dengan Jurusan Tarbiyah STAI Sangatta Kab. Kutai Timur., 2024)
The crime of trafficking in persons, especially in sexual exploitation, is still common in Indonesia. So that the existence of this criminal act injures the ethics of life which has been implied in the TAP MPR RI Number VI / MPR / 2001, also considering that the victims, who are mostly women and children, need legal protection from a victimology perspective. So from here the writer wants to discuss about knowing the criminal law policy of sexual exploitation in Indonesia and analyzing the policy from a victimology perspective. The method used by the author is normative juridical by reviewing the current criminal law policy on child sexual exploitation as well as how the viewpoint is from a victimological perspective. In the regulation of the crime of trafficking in persons in Law Number 21 of 2007, there are three main elements, namely the recruitment / sending / acceptance of persons, the existence of coercion or threats, and finally the goal is to lead to sexual exploitation or other forms. And in Law Number 35 of 2014 concerning child protection it also regulates this and the two regulations regulate slightly different protection. In the victimology of legal protection from the law on trafficking in persons, it is more repressive in nature, while the child protection law has preventive and repressive stages and the second punishment given to the perpetrator is also severe for the justice of the victim.